Strong coupling and energy funnelling in an electrically conductive organic blend. Issue 33 (20th July 2020) - Rahme, Matthew S.; Sabatini, Randy P.; McGregor, Sarah K. M.; Wawrzinek, Robert; Namdas, Ebinazar B.; Lo, Shih-Chun; Lakhwani, Girish
Abstract : A host–guest matrix enables both strong exciton-photon coupling and efficient energy transfer. This combination holds promise toward reduced laser thresholds and eventual electrical injection. Abstract : Strong coupling between an exciton and a cavity photon mode offers the promise of lower lasing thresholds, which has attracted interest in organic systems working toward electrically injected lasing. However, current organic polariton lasers have yet to exhibit thresholds beyond the reach of traditional lasers. Here, we investigate the possibility of energy funnelling from host to guest in a polariton system. We construct a material blend containing a dithiophenyl diketopyrrolopyrrole dye with an electrically conductive fluorene–benzothiadiazole co-polymer matrix. We demonstrate that a polariton system can exhibit efficient host to guest energy transfer while maintaining both strong exciton–polariton coupling and polariton emission. We expect that energy funnelling will become an important tool to drive down polariton laser thresholds in organic systems.